A Comprehensive Review on Cloud Computing Security - Chinmay Teni; Aditya Nawale (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Cloud computing is the model that enables service providers to deliver computing resources over the Internet. Virtualization, pay-as-you-go model, and scalability features of cloud computing make it to be adopted by a diversified set of organizations and individuals. Security, in case, vendor lock-in, data lock-in, load balancing, and resource allocation are major issues associated with cloud computing technology. In this paper, authors have comprehensively studied cloud security issues and analyzed existing solutions to cloud computing security.